2020
DOI: 10.1371/journal.pone.0237333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and associated factors among adult residents in Arba Minch Health and Demographic Surveillance Site, Southern Ethiopia

Abstract: Hypertension is the leading risk factor for mortality and it is also one of the major risk factors for other non-communicable diseases (NCDs). The objective of the study was to assess the prevalence of hypertension and its associated factors among adults residing in Arba Minch health and demographic surveillance site (HDSS), Southern Ethiopia. A community-based cross-sectional survey was conducted in 2017 on the estimated sample size of 3,368 adults at Arba Minch Health and Demographic Surveillance site (HDSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
4
21
0
Order By: Relevance
“…Moreover, the present study also claimed that participants who consumed fruits daily were less likely to have hypertension. is is similar to previous studies [11,12]. It is also further supported by interventional studies that claim that fruit consumption is effective in lowering BP through increasing the antioxidants that are responsible for the reduction of free radicals [34,35].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, the present study also claimed that participants who consumed fruits daily were less likely to have hypertension. is is similar to previous studies [11,12]. It is also further supported by interventional studies that claim that fruit consumption is effective in lowering BP through increasing the antioxidants that are responsible for the reduction of free radicals [34,35].…”
Section: Discussionsupporting
confidence: 89%
“…In the last few years, the lifestyle of the Ethiopian population is changing due to urbanization and demographic transition [10]. As a result, risky health behaviors (smoking, alcohol consumption, sugar intake, and fatty meal commotion) are being increased and predispose the population to various noncommunicable diseases including hypertension [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this subcategorical analysis, 20 studies were included for the assessment of age as a risk factor for hypertension. 20,22,[24][25][26][27][28][30][31][32][33]37,38,[42][43][44][49][50][51][52] P Association of sex with hypertension F I G U R E Forest plot of odds ratio for the association of male sex with hypertension.…”
Section: Association Between Age and Hypertensionmentioning
confidence: 99%
“…Contrary to certain authors [ 13 , 29 ], the subjects who declared that they did not regularly consume vegetables had developed significantly more hypertension than those who consumed them (aOR = 1.35 [1.02–1.80]; p =0.038). A recent Ethiopian study found that increasing the consumption of fruits and vegetables reduced the likelihood of hypertension among study participants [ 44 ]. Likewise, meta-analysis reports have shown that increasing fruit and vegetable consumption prevents the risk of developing hypertension [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%